Макет экспериментальной установки для исследования пространственно-временного интегрирования в акустооптической среде - Rudiakova, A. N.; Lipinskii, A. Yu.; Danilov, V. V. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
Experimental studies of spatio-temporal integration in an acousto-optic medium have been carried out, and a functional model of the interaction between acoustic and optical pulse sequences in the aperture of an acousto-optic modulator, corresponding to the prototype of the experimental setup, has been developed. The experimental data confirm the modeling results and allow the conclusion to be drawn regarding the correctness and adequacy of the proposed model.